An Analysis of High School Students' Mathematical Representation Skills on Relations and Functions - Putri, Nathania Salsabila; Riyanti , Asifa Ajeng Dwi; Saputri , Hana Febri; Wahyuni , Reni; Ullah , Naqeeb (EDUPEDIA Publisher, 2024)
This research was carried out with the aim of analyzing the abilities of high school level students in solving relationship and function problems. This research method is a qualitative method with descriptive research type. This research was carried out at one of Pekanbaru High School with subjects in classes X.1 and X.2 at YLPI Pekanbaru High School, with a total of 6 students. The data collection technique used in this research is a written test technique in the form of a description consisting of 2 questions. After the students have completed the questions, the results of the answers will be analyzed by the researcher as a percentage of the students' results and the researchers will conduct interviews with the students regarding the answers they made. Based on the research results, the percentage of the